Amyloidosis in association with spontaneous feline immunodeficiency virus infection. Issue 4 (April 2013) - Asproni, Pietro; Abramo, Francesca; Millanta, Francesca; Lorenzi, Davide; Poli, Alessandro
Tissues from 34 naturally feline immunodeficiency virus (FIV)-infected cats, 13 asymptomatic cats and 21 cats with signs of feline acquired immunodeficiency syndrome (F-AIDS), and 35 FIV-seronegative subjects were examined to determine the presence of amyloid deposits. Twenty experimentally FIV-infected cats and five specific pathogen-free (SPF) control cats were also included in the study. Paraffin-embedded sections from kidney and other organs were submitted to histological and histochemical analysis. Amyloid deposits were identified by a modified Congo red stain and confirmed by electron microscopy to demonstrate the presence of amyloid fibrils in amyloid positive glomeruli. In all positive cases, secondary amyloidosis was identified with potassium permanganate pretreatment and amyloid type was further characterised by immunohistochemistry using primary antibodies against human AA and feline AL amyloids. Amyloid deposits were present in different tissues of 12/34 (35%) naturally FIV-infected cats (seven presenting F-AIDS and five in asymptomatic phase) and in 1/30 FIV-seronegative cats. All the experimentally FIV-infected and SPF subjects showed no amyloid deposits. Amyloidosis has been reported in human lentiviral infections, and the data reported here demonstrate the need, in naturally FIV-infected cats, to consider the presence of amyloidosis in differential diagnosis of hepatic and renal disorders to better assess the prognosis of the disease.